Pengaruh Penerapan Model Pembelajaran Klasikal pada Asfek Perkembangan Anak Usia Dini di TK Al Falah - Eni Nuraeni; Ema Hanapiah; Novi Yanti Ulpah (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2022)
Children aged 0 to 5 years is a golden age (golden age). This period is an ideal time for children to seek, learn and acquire basic concepts that affect children's lives in the future. The implementation ofthe classical learning model applied in PAUD institutions has notfully referred to the 2013 curriculum menu. Then where PAUD teaching staffis still minimal, there are junior and senior high school graduates or undergraduates who have not graduated so that in practice it does not run optimally. This study aims to describe how the implementation of the classical learning model in Al Falah Kindergarten, Langkaplanca District. The method in this research is observation and interview. The data obtained are primary data. The results of the observations show that the implementation of the application of the classical learning model is of "Less" quality, and learning in Al Falah Kindergarten is mostly dominated by moral and religious aspects, every day there must be reading and writing Iqra, and it's all on the demands of parents. Because many parents question ancient learning, other aspects do not appear. Based on the results of the study, it can be concluded that the implementation of the application of the classical learning model can affect the developmental aspects of children in Al Falah Kindergarten, Langkaplancar District, seen from the results of observations that are of "Less" quality. It is hoped that it can improve the quality of learning at Al Falah Kindergarten, Langkaplancar District so that it is betterfor the future in order to optimize all aspects of child development.